Model Penilaian untuk Kematangan Perencanaan Keselamatan dalam Tahap Pra Konstruksi - Endroyo, Bambang; Suraji, Akhmad (Department of Civil Engineering, Diponegoro University, 2014)
The construction sector still has a low achievement in safety issues. Fatal accident rate in construction is higher than average rate in other industries. Because of it, need some attention to minimize the rate of accident in construction. This research examined the key factors of safety planning in the pre-construction stage, and it was based on the theories of accidents causation having the upstream approach. Some theories were: Constraint-Response Theory (CR); Construction Design Management (CDM), and the Process Protocol (Pp). This research broke down the three theories above (CR; CDM; Pp) into the concept of the key factors of safety planning in pre-construction. Then, the concept was verified by construction practitioners and academician, using Delphi method three rotations. During the verification, from the first to the third round, there were reduction and the addition concept and language appropriateness. The findings of this research were assessment models of maturity safety planning in the pre construction stages. There were two models, the model of